PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING PEMBELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN UNTUK KELAS V SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the problem-based learning (e-module) model on mathematics learning on addition and subtraction of fractions for fifth-grade elementary school students at SD Negeri 129 Palembang. This study employed a research design that included definition, planning, and development. Data analysis included validity analysis, practical analysis, and effectiveness analysis. The results showed a significant effect of the use of the e-module on addition and subtraction of fractions for fifth-grade students at SD Negeri 129 Palembang. The three analyses showed that the e-module on addition and subtraction of fractions for fifth-grade students was highly valid, very practical, and very effective. Keywords: Problem-Based Learning, Addition and Subtraction Of Fractions, Mathematics